Endobronchial tuberculosis complicated with Staphylococcus aureus pneumonia and empyema in a child - Uzuner, Nevin; Anal, Ozden; Karaman, Ozkan; Sevinç, Can; Türkmen, Mehmet; Canda, Tülay; Kazan, Eyüp (The Turkish Journal of Pediatrics, 2003)
Childhood tuberculosis might have unusual clinical presentation. A seven-year-old female patient was admitted with fever and pleural effusion. Her pneumonia resolved following 21-day treatment period. An atelectatic appearance remained on the right middle zone in her chest X-ray. Tuberculin skin test showed 13 mm induration. Triple drug antituberculosis treatment was started. Since atelectasis persisted on her follow-up radiograph one month later, bronchoscopy was performed which revealed a hemorrhagic polypoid mass occluding the right upper lobe anterior segment orifice. Surgical removal was performed by right upper lobectomy. The pathological diagnosis was necrotizing granulomatous infection suggesting tuberculosis. The patient has been well on follow-up after completing a nine-month course of antituberculous treatment.